Trap rebuilding by Myrmeleon brasiliensis larvae (Neuroptera: Myrmeleontidae) in response to flooding: the effect of body size - de Oliveira Leite, Vitor Gabriel (2021)
Introduction: Immature forms of the antlion Myrmeleon brasiliensis (Neuroptera, Myrmeleontidae) build traps in dry sandy soil to capture prey. Objective: The aim of the present study was to investigate how the waterlogging of the soil due to rain affects the trap rebuilding and relocation behavior of M. brasiliensis of different sizes. Methods: The study was conducted between July and December 2019. Larvae M. brasiliensis were observed and collected from a forest reserve in the municipality of Aquidauana in the state of Mato Grosso do Sul, Brazil. Results: In the natural environment, most larvae rebuilt their traps in the same location seven days after the simulation of rain, with a smaller diameter than that observed prior to the simulation of rain. In the laboratory, the movements of M. brasiliensis larvae and rebuilding of the traps after the waterlogging of the soil was affected by body size. Larger larvae moved more and were more likely to rebuild their traps. Conclusions: The saturation of the soil affects the foraging of M. brasiliensis larvae, which are impeded from rebuilding their traps for a period. In situations of long periods of saturated soil, the mortality rate of the larvae is high and rebuilding of the traps occurs after the soil dries out, but with a smaller trap size. These data suggest that changes in the rainfall pattern can affect the population structure of M. brasiliensis larvae, with the selection of larger individuals in situations of more severe rains. In this process, the smaller larvae are more affected, as their foraging is impeded.